2016
DOI: 10.2147/ijn.s101294
|View full text |Cite
|
Sign up to set email alerts
|

The role of well-defined nanotopography of titanium implants on osseointegration: cellular and molecular events in vivo

Abstract: Purpose Mechanisms governing the cellular interactions with well-defined nanotopography are not well described in vivo. This is partly due to the difficulty in isolating a particular effect of nanotopography from other surface properties. This study employed colloidal lithography for nanofabrication on titanium implants in combination with an in vivo sampling procedure and different analytical techniques. The aim was to elucidate the effect of well-defined nanotopography on the molecular, cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…This assumption is supported by an in vitro study showing that a murine-macrophage (RAW264.7) increased the expression of TNF-α in response to surfaces with a groove-shaped nano-topography [32]. Another plausible explanation is that the macrophage response is also dependent on other surface characteristics, including surface chemistry, regardless of whether it is HA, as in the present study, or titanium, as in the previous in vivo study [46]. The influence of chemistry in relation to nano-topography has been previously addressed in an in vivo study, where nano-topography did not modify the in vivo bone response to the same extent as the chemistry did [47].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This assumption is supported by an in vitro study showing that a murine-macrophage (RAW264.7) increased the expression of TNF-α in response to surfaces with a groove-shaped nano-topography [32]. Another plausible explanation is that the macrophage response is also dependent on other surface characteristics, including surface chemistry, regardless of whether it is HA, as in the present study, or titanium, as in the previous in vivo study [46]. The influence of chemistry in relation to nano-topography has been previously addressed in an in vivo study, where nano-topography did not modify the in vivo bone response to the same extent as the chemistry did [47].…”
Section: Discussionsupporting
confidence: 79%
“…This finding implies an association between nano-topography and increased pro-inflammatory activity. In contrast, a recent in vivo study has shown that titanium implants with controlled nano-topography (80 nm hemispherical protrusions) resulted in the lower recruitment of macrophages and lower TNF-α expression in the implant-adherent cells compared with implants without nano-topography [46]. One plausible explanation is that the effect of nano-topography on macrophages is dependent on the shape and size of the nano-features.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced osseointegration has frequently been observed in cases where modified Ti substratum have been implanted into an animal model, and under conditions where the Ti implants are exposed to normal bodily fluids and proteins [ 34 , 35 , 36 ]. A study investigating the implantation and response of a modified Ti surface possessing titanium dioxide nanorods in rabbit femurs achieved better osseointegration and higher rates of bone tissue apposition of the nanostructured Ti, compared to classically treated (acid etched, grit blasted) micro-rough Ti surfaces [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, there is a growing body of evidence about the direct and rapid influence of implant surface treatments on the modulation of the expression of chemokine receptors that are important for cell recruitment and adhesion, both processes being crucial for the inflammatory and regenerative processes in vivo ( 110 , 111 ). An appropriate implant surface may attenuate the inflammatory response while enhancing mineralization during osseointegration, as shown for implants with nano-surfaces ( 112 ) or the synthetic lipid polymer 2-methacryloyloxyethyl phosphorylcholine ( 113 ).…”
Section: Therapeutic Prospects For the Chemokine System In Ppol/almentioning
confidence: 99%